Phillips' science of dental materials 2026-02-15T20:46:22+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Anusavice, Kenneth J; Phillips, Ralph W (Saunders, 2003)

(untitled)
This thoroughly revised text covers the most current dental materials available. Among the features are hundreds of high-quality illustrations and clinical photos to aid in learning the step-by-step process of important procedures